If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -6x = -3x + 10 Reorder the terms: 15 + -6x = 10 + -3x Solving 15 + -6x = 10 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 15 + -6x + 3x = 10 + -3x + 3x Combine like terms: -6x + 3x = -3x 15 + -3x = 10 + -3x + 3x Combine like terms: -3x + 3x = 0 15 + -3x = 10 + 0 15 + -3x = 10 Add '-15' to each side of the equation. 15 + -15 + -3x = 10 + -15 Combine like terms: 15 + -15 = 0 0 + -3x = 10 + -15 -3x = 10 + -15 Combine like terms: 10 + -15 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667
| 3x+1=4x+2-x | | 3x+42+4x+140=-21 | | 63-x/.4 | | -9=0.16666666666z-11 | | Z/4=-8 | | -x+7=-4x-5 | | -15x=-5x+10 | | -15x=-5a+10 | | (2+y)2=6 | | 6-15/5*8 | | 10x-12=11x-7 | | 1160-125p=165p | | -[7z(14z+10)]=10+(6z+1) | | 72=-3h+6h | | 9P+7-4P=-6P-12 | | m+24=155 | | -6x+9y=25 | | 20-4=6x-3x+7-3+x | | -7x-7=5x+5 | | -(62+x)=-248 | | n-3+2=24 | | g(x)=-1/4x^2-13 | | 3-3(x-4)=-3-2(5-x) | | 10-(2y+5)=2y-5 | | -4(v+2)+2v+7=7v+12 | | f(x)=-x^2-48 | | -(-x+18)= | | 8x+7=-3(5x-4) | | y*2+9y*2= | | m-15=3(m-4)-2m | | 617=25k-8 | | 9(p-8)=18 |